Alvarado score in acute appendicitis: revisited - Seshadri, Lakshmi Narayanan; Baya reddy, Preethi; Mohan, L. N. (International Surgery Journal, 2019)
Background: Acute appendicitis is a common surgical emergency and preoperative diagnosis may be difficult. The Alvarado scoring system has been widely used for predicting the probability of acute appendicitis. The aim of this study was to assess the positive predictive value of Alvarado scoring system in acute appendicitis. Methods: We retrospectively analyzed two hundred and four adult patients who were operated for suspected acute appendicitis between September 2003 and August 2008. Results: Patients with Alvarado scores more than 6 were most likely to have acute appendicitis. Patients with biopsy confirmed acute appendicitis had a mean score 6.16±1.84 (p=0.0001). Patients with histopathology showing no acute appendicitis had a mean score of 4.15±1.86 (p=0.0001). The overall positive predictive value of the Alvarado scoring is 95 and. Conclusions: The Alvarado score is useful in diagnosing acute appendicitis and a high score strongly correlates with a definitive operative and histopathological diagnosis of acute appendicitis. We propose that a diagnosis of acute appendicitis can be made with a score of >6 as compared to a score of >8 as described in literature.